ETHICS IN MARKETING - BRANDS MUST WORK WITH TRANSPARENCY AND CONSUMER TRUST (Modern education and development, 2025)
In this article, we consider ethical issues in marketing, with an emphasis on the need for brands to work with transparency and consumer trust. Special attention is paid to the practices of honest and open communication with the target audience, compliance with standards of social responsibility and consumer protection. In the face of increasing competition and increased consumer expectations, brands must not only offer high-quality products and services, but also maintain trusting relationships with customers. В статье мы рассматриваем вопросы этики в маркетинге, с акцентом на необходимость работы брендов с прозрачностью и доверием потребителей. Особое внимание уделяется практикам честного и открытого общения с целевой аудиторией, соблюдению стандартов социальной ответственности и защите интересов потребителей. В условиях роста конкуренции и повышенных ожиданий со стороны потребителей, бренды должны не только предлагать качественные товары и услуги, но и поддерживать доверительные отношения с клиентами.